2023
DOI: 10.1101/2023.01.04.522691
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unravelling cell type specific response to Parkinson’s Disease at single cell resolution

Abstract: Parkinsons Disease (PD) is the second most common neurodegenerative disorder and is generally characterized by impaired motor functions. It currently affects 6.3 million people aged 60 years and more, worldwide. The pathological hallmarks of PD are Lewy bodies (abnormal aggregation of α-synuclein inside cells), which are observed primarily in the substantia nigra (SN) region of the midbrain. It is yet not known how different cell types in SN respond during PD and what are the molecular mechanisms underlying ne… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…scRNA-Seq Characterization of Immune Cell Clusters in Line 61-PFF Mice. Several scRNA-Seq studies point to the heterogeneity of cells involved in PD pathogenesis (51)(52)(53)(54). To identify cell-speci c contributions in the Line 61-PFF model, we performed scRNA-Seq on sorted CD45 + leukocytes obtained from Line 61 mice injected with PBS, monomer, PFF plus VH, or PFF plus AZD1480 (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…scRNA-Seq Characterization of Immune Cell Clusters in Line 61-PFF Mice. Several scRNA-Seq studies point to the heterogeneity of cells involved in PD pathogenesis (51)(52)(53)(54). To identify cell-speci c contributions in the Line 61-PFF model, we performed scRNA-Seq on sorted CD45 + leukocytes obtained from Line 61 mice injected with PBS, monomer, PFF plus VH, or PFF plus AZD1480 (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several scRNA-Seq studies have focused on T-cells isolated from the blood and cerebrospinal uid of PD patients, demonstrating the differentiation and expansion of peripheral CD8 + T-cells and CD4 + T-cells, as well as the interaction of peripheral CD4 + T-cells with endothelial cells in PD patients(53, 88, 89). A recent snRNA-Seq study revealed an increased frequency of T-cells within the SNpc from postmortem PD patients(52). However, little is known about the transcriptional features of T-cells in PD, especially Tcells in ltrating the CNS.…”
mentioning
confidence: 99%
“…Glial cells from the PD midbrain showed enrichment for microglia in an activated state and astrocytes at the end of astrogliosis [36], while microglia from the SN showed transcriptional evidence for the cytokine-mediated signaling pathway that strengthened with advancing PD pathogenesis [56]. In fact, an independent snRNA-seq analysis identified a transcriptionally distinct microglia subtype overrepresented in the PD SN that showed differential expression of ST6GAL1, which has been shown to promote sustained signaling through the NFκB and JAK/ STAT inflammatory pathways [48,58]. Taken together, these snRNA-seq analyses of the PD midbrain support both the increase in immune cells and upregulation of immune responses uncovered by the differential gene expression signals associated with neuroinflammation that were observed at a bulk resolution.…”
Section: Glial Cells Activate Inflammatory Pathways In Pdmentioning
confidence: 97%
“…Second, an analysis of oligodendrocytes from the PD midbrain identified differentially expressed genes (DEG) in synaptic transmission pathways compared to non-PD controls, which coincided with a reduced fraction of myelinating oligodendrocytes in PD samples [36]. Third, an oligodendrocyte subtype, whose transcripts were enriched for processes linked to synapse organization, was found to be depleted in PD samples compared to non-PD controls [48]. Indeed, oligodendrocytes are critical in the maintenance of synaptic function in a healthy state [49], yet the snRNA-seq data suggest that a subset of oligodendrocytes lose their preservative functions in PD pathology.…”
Section: Synaptic Dysfunction May Contribute To Dan Susceptibility In Pdmentioning
confidence: 99%
See 1 more Smart Citation